Innovation cycles and productivity gain in the maritime transport (ship structure and navigation) - Ho, Zi Hui (2018)
Innovation is a constant within the maritime transport. As new technologies and practices are developed, the industry often benefits with higher productivity. However, the innovation process is more than just plain development and implementation as they are many factors of considerations to justify the investments. As such, this report serves to define the concepts of innovation and productivity, identify the drivers and barriers towards innovation within the maritime industry as well as to determine the relationship between innovations and productivity gains. Additionally, it aims to quantify productivity gains in monetary terms due to inadequate research done with respect to these kinds of measurements. Innovations in the aspect of ship structure and navigation will be the focus of this report. Three innovations from the two fields were chosen for analysis: (1) composite materials, (2) X-bow/wave-piercing hull and (3) unmanned autonomous vessels. The methodology of this report involves detail analysis of past research where relevant information were gathered for calculations of productivity gains, primarily in terms of fuel cost savings from the shipowners’ perspective, to be carried out. The calculations are further substantiated by interviews conducted with relevant industry professionals, as well as to conduct a technological forecast for the chosen innovations based on the views and opinions of the interviewees. Firstly, composite materials bring about a weight reduction to the vessel which was simulated at between 20 – 40% in this report. Based on the calculations carried out, it is found that potential fuel cost savings with the use of composite cargo ships amounted to between $100,000 to $160,000 per annum for a Kamsarmax vessel. Next, the X-bow/wave piercing hull, which depends on the wave cancellation theory, provides a reduction in wave-making resistance during ship motion. Resistance reduction percentages were simulated at between 10 – 30% and corresponding decrease in fuel costs for a Very Large Crude Carrier were obtained at between $1 million to $2.5 million per year. Finally, the employment of a fully unmanned autonomous Panamax vessel was experimented and relevant cost savings that include crew and fuel costs were calculated at approximately US$800,000 and US$130,000 per annum respectively. Through the professional interviews, the likelihoods of the materialisation of the innovations were also drawn. Overall, this research hopes to be a reference to industry players in the assessments of these forthcoming innovations and also aid in decisions to invest.